Nutritional status and food consumption of patients with Parkinson disease - Fernandez, Raissa Dias; Campos, Jamilie Suelen dos Prazeres; Santos, Thais de Oliveira Carvalho Granado (Arquivos de Neuro-Psiquiatria, 2021)
Background: Parkinson's disease (PD) is a neurodegenerative disease that affects food intake as the disease progresses. The assessment of nutritional status is essential to identify early nutritional deficits. Objective: To investigate the nutritional status and food intake of patients diagnosed with PD. Methods: This was a descriptive, cross-sectional, and quantitative study. A structured questionnaire with restricted questions was applied to identify the sociodemographic profile and anthropometric measurements were taken. To evaluate the disease stage, the modified Hoehn & Yahr scale was used. Food intake was evaluated using the Food Frequency Questionnaire (FFQ). The acquired information was organized in the Microsoft Office Excel 2010 program and statistical analysis was performed using the BioEstat 5.3 program. Results: The research was carried out with 40 patients; the majority was male (60%), over 60 years old (52.5%), single (55%), with a high school degree (42.5%), retirees (80%), and receiving one minimum salary (42.5%). Most were classified with eutrophic (42.5%) and overweight (42.5%). About food consumption, the most common foods were banana (60%), fish (52.5%), acerola (45%), and orange (32%). Among the high-risk foods, red meat (82.5%), fried foods (30%), heavy cream (25%), and filled sandwich cookies (25%) were the most common. Conclusions: Most patients had a high consumption of red meat and processed foods, with relevant consumption of some fruits and low consumption of grains and oilseeds. The disease stage was not associated with nutritional status.
Keywords: Nutritional Status; Eating; Parkinson Disease